Pengaruh lingkungan sekolah dan kualitas guru terhadap prestasi belajar siswa kelas XII pada SMK Kencana Tenjo - Purnamasari, Cacita; Sutomo; Suhartono (Universitas Tangerang Raya, 2024)
Student academic achievement refers to the results or academic accomplishments attained by a student in terms of knowledge, skills, and understanding of the subjects taught in school or other educational institutions. This research aims to analyze the influence of the school environment and teacher quality on student academic achievement among 12th-grade students of the 2016-2020 cohort at Kencana Tenjo Vocational High School (SMK). The research employs a quantitative approach. The population in this study comprises 555 12th-grade students of SMK Kencana Tenjo during the years 2016-2020. The study utilizes a random sampling method, resulting in 85 respondents. The method applied in this research is multiple linear regression analysis using SPSS software version 25. The research findings indicate that both the school environment and teacher quality have a positive and significant partial influence on student academic achievement. Moreover, collectively, the school environment and teacher quality can influence the academic achievement of SMK Kencana Tenjo students by 81.1%.Student academic achievement refers to the results or academic accomplishments attained by a student in terms of knowledge, skills, and understanding of the subjects taught in school or other educational institutions. This research aims to analyze the influence of the school environment and teacher quality on student academic achievement among 12th-grade students of the 2016-2020 cohort at Kencana Tenjo Vocational High School (SMK). The research employs a quantitative approach. The population in this study comprises 555 12th-grade students of SMK Kencana Tenjo during the years 2016-2020. The study utilizes a random sampling method, resulting in 85 respondents. The method applied in this research is multiple linear regression analysis using SPSS software version 25. The research findings indicate that both the school environment and teacher quality have a positive and significant partial influence on student academic achievement. Moreover, collectively, the school environment and teacher quality can influence the academic achievement of SMK Kencana Tenjo students by 81.1%.